2021
DOI: 10.3390/v13030512
|View full text |Cite
|
Sign up to set email alerts
|

Repeated SARS-CoV-2 Positivity: Analysis of 123 Cases

Abstract: Repeated positivity and reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is a significant concern. Our study aimed to evaluate the clinical significance of repeatedly positive testing after coronavirus disease 2019 (COVID-19) recovery. We performed a systematic literature search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. With available individual patient data reporting on repeatedly SARS-CoV-2 positive (RSP) patients, case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…On the contrary, a higher requirement of ICU admission and mechanical ventilation was observed during reinfection in our review. A meta-analysis analysis of 123 cases by Vancsa et al[96] showed that the second episode of SARS-COV-2 infection is more severe than the first if it happens within 60 days of the first positive PCR. This deems the necessity of IPD analysis as many of the larger case series report more severe cases which might skew the overall findings.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a higher requirement of ICU admission and mechanical ventilation was observed during reinfection in our review. A meta-analysis analysis of 123 cases by Vancsa et al[96] showed that the second episode of SARS-COV-2 infection is more severe than the first if it happens within 60 days of the first positive PCR. This deems the necessity of IPD analysis as many of the larger case series report more severe cases which might skew the overall findings.…”
Section: Discussionmentioning
confidence: 99%
“…At least every patient received 4 COVID-19 PCR tests during his/her hospital stay. Concerning RT-PCR in urine and respiratory samples, viral RNA was extracted from 300 µL of urine and 300 µL of Naso-pharyngeal swab samples with an automated extraction instrument according to the manufacturer’s protocol (TanBead, Taiwan Advanced Nanotech Inc., Taiwan,) and previous scientific evidence (results as described previously) [ 12 ]. SARS-CoV-2 were detected by a real-time reverse transcription polymerase chain reaction (RT-PCR) assay using the Allplex™ SARS-CoV-2 Assay kit according to the manufacturer’s protocol (Seegene Inc., Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, while rRT-PCR by a nasopharyngeal swab is a well-defined method for the diagnosis of COVID-19, little data exist to assess the role of positive rRT-PCR in other biologic samples and its possible correlation with the disease severity and infectiousness to others [8][9][10]. In fact, disease severity is triggered by several predisposing factors, including viral shedding, that could be related to the immune response and infection control [11,12]. Indeed, COVID-19, as previously suggested, which shows systemic involvement [13], is also characterized by endothelium damage with an increase in fibrinogen serum levels [14] and is correlated to a worse prognosis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the prevalence of reinfection after recovery from COVID-19 was very low and that prior infection with SARS-CoV-2 conferred an 80% protective efficacy against reinfection (assuming baseline prevalence of 5%). The existing reviews (23,(85)(86)(87)(88)(89)(90)(91)(92)(93)(94) have not examined the question of prevalent immunity sufficiently (Supplementary Table 4).…”
Section: Comparison Of Risk Of Sars-cov-2 Infection Between Individuals With and Those Without Prior Infectionmentioning
confidence: 99%